2008
DOI: 10.1159/000135669
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Different Tetrafluorides on Erosion of Pellicle-Free and Pellicle-Covered Enamel and Dentine

Abstract: The aim was to analyze the protective effects of titanium, zirconium and hafnium tetrafluorides on erosion of pellicle-free and pellicle-covered enamel and dentine in vitro. Eight groups of 20 specimens each of bovine enamel and bovine dentine were prepared. Half the specimens in each group were immersed in human saliva for 2 h for pellicle formation. Specimens were then left untreated (controls) or were treated for 120 s with TiF4, ZrF4 or HfF4 solutions (0.4 or 1%) or 1.25% A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
1
21

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 52 publications
1
55
1
21
Order By: Relevance
“…In a previous study it was shown that the capacity of TiF 4 to protect dentin against erosive calcium loss was better in pellicle-covered than in pellicle-free samples. 12 As shown previously, the surface concentration of titanium was significantly increased after application of TiF 4 at pH 1.2. 24,25 The fluoride surface concentration was also increased compared to the control, although not significantly, and was in the range found previously for TiF 4 -treated dentin.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In a previous study it was shown that the capacity of TiF 4 to protect dentin against erosive calcium loss was better in pellicle-covered than in pellicle-free samples. 12 As shown previously, the surface concentration of titanium was significantly increased after application of TiF 4 at pH 1.2. 24,25 The fluoride surface concentration was also increased compared to the control, although not significantly, and was in the range found previously for TiF 4 -treated dentin.…”
Section: Discussionsupporting
confidence: 67%
“…The efficacy of TiF 4 to reduce carious demineralisation suggested that it might be also an effective agent in preventing erosive dental loss. In several recent in vitro 3,[11][12][13] and few in situ studies 14,15 it was shown that TiF 4 reduced dental erosion significantly and was more effective than sodium, amine or stannous fluoride.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 However, even though TiF 4 was shown to be more effective to prevent erosive demineralisation than sodium, stannous or amine fluoride, 2-5 most studies found that TiF 4 is not able to protect enamel erosion completely. [5][6][7][8] Previous experiments showed that CO 2 laser irradiation induced a melting and recrystallinization process resulting in an increased acid resistance of dental hard tissues. [9][10][11] Moreover, laser irradiation might be also an approach to increase the efficacy of different fluoride solutions, such as amine 12 or sodium fluoride, 13,14 to reduce acid demineralisation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other studies investigating dentine wear by either tooth brushing [20,21], erosion [22,23] or combination of both [2,24] also use bovine teeth to substitute human dentine. When using bovine teeth, it is easy to obtain more than one sample per tooth allowing allocation of samples from the same tooth to different experimental groups, thus increasing comparability between those groups [25].…”
Section: Discussionmentioning
confidence: 99%